Total Team Collapse in the 2014 FIFA World Cup semi-final (Brazil 1 - Germany 7): Implications for Coaching and Sport Psychology practice - Filho, E. (International Journal of Sport Psychology, 2021)
To inform the development of athletes and teams, an applied analysis of the factors contributing to the team collapse experienced by the Brazilian soccer team against Germany during the 2014 FIFA World Cup semi-final is presented. Specifically, the iterative role of individual players, team processes, and contextual factors in the team collapse experienced by the Brazilian team is discussed within a multi-layered view of performance. Applied recommendations to circumvent the absence of key players in decisive matches, faulty team processes in high pressure situations, and home field disadvantage in playoff stages of knockout tournaments are offered.